Wealth inequality and CO₂ emissions in emerging economies: The case of BRICS - Goodness C. Aye (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
As the world battles with the triple problems of social, economic, and environmental challenges, it has become important to focus both policy and research efforts on these. Therefore, this study examines the effect of wealth inequality on CO2 emissions in five emerging economies: Brazil, Russia, India, China, and South Africa. The top decile of wealth share was used as a measure of wealth inequality, while CO2 emissions per capita were used as a measure of CO2 emissions. GDP per capita, population, and financial development (domestic credit to the private sector) were included as control variables. A balanced panel dataset of annual observations from 2000 to 2014 for these countries was used. Both fixed and random effects panel models were estimated, but the Hausman test favoured the use of the fixed effects model. The results based on the fixed effects panel regression model show that wealth inequality, GDP per capita, and population have positive effects on CO2 emissions, while financial development has a negative effect.
Keywords: C23; D31; Q52; Q54; 330; CO2 emissions; emerging economies; fixed effects; random effects; wealth inequality